2016
DOI: 10.1016/j.carbon.2015.08.075
|View full text |Cite
|
Sign up to set email alerts
|

Chirality dependent corona phase molecular recognition of DNA-wrapped carbon nanotubes

Abstract: a b s t r a c tCorona phase molecular recognition (CoPhMoRe) is a phenomenon whereby a polymer or surfactant corona phase wrapped around a nanoparticle selectively recognizes a particular molecule. The method can potentially generate non-biological, synthetic molecular recognition sites, analogous to antibodies, for a broad range of biomedical applications, including new types of sensors, laboratory and clinical assays, as well as inhibitors and targeted therapeutics. In this work, we utilize near infrared flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 42 publications
2
81
0
Order By: Relevance
“…47,55,58,62,[66][67][68][69] Pan et al 55 demonstrated a multiplexed optical sensing scheme for co-factor heme and its precursory porphyrins. 47,55,58,62,[66][67][68][69] Pan et al 55 demonstrated a multiplexed optical sensing scheme for co-factor heme and its precursory porphyrins.…”
Section: Optical Swcnt Sensors For Chemicals and Biomoleculesmentioning
confidence: 99%
“…47,55,58,62,[66][67][68][69] Pan et al 55 demonstrated a multiplexed optical sensing scheme for co-factor heme and its precursory porphyrins. 47,55,58,62,[66][67][68][69] Pan et al 55 demonstrated a multiplexed optical sensing scheme for co-factor heme and its precursory porphyrins.…”
Section: Optical Swcnt Sensors For Chemicals and Biomoleculesmentioning
confidence: 99%
“…nIR fluorescent single SWCNTs are versatile building blocks for biosensors and demonstrate detection limits down to single molecules (9)(10)(11)(12)(13). We selected the neurotransmitter dopamine for this study because of its central role for reward control and learning and because it is one of the neurotransmitters for which volume transmission is heavily discussed (14,15).…”
mentioning
confidence: 99%
“…This range covers the requisite excitation maxima to visualize fluorophores and all excitation peaks of a typical SWCNT multi-chirality sample ( Fig. 2A; Bachilo et al, 2002;Miyauchi et al, 2004;Salem et al, 2016). A shutter is used to allow illumination only during sampling.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1; Kruss et al, 2014). (B) nIR fluorescence spectrum (785 nm excitation) of (GT) 15 −SWCNT before and after addition of 100 μM dopamine in PBS (raw data; Kruss et al, 2014) (C) Deconvolution of a fluorescence spectrum of (GT) 15 -wrapped SWCNT: Original spectrum (blue curve), individual chirality contributions (dashed black curves) and the sum of the individual peaks (dashed red curve; Salem et al, 2016). SWCNT, single-walled carbon nanotubes; nIR, near infrared.…”
Section: Neurotransmitter Recognition Using Neurosensorsmentioning
confidence: 99%